Medication adherence among people of Indian ethnicity living with chronic disease following migration to Australia. Issue 2 (April 2020) - Singh, Charanjit; Crawford, Kimberley; Willey, Suzanne; Hall, Helen; Harder, Karen; Plummer, Virginia; Williams, Allison
Abstract: Background: The self-management of chronic conditions is challenging for culturally and linguistically diverse populations who have migrated to predominantly English-speaking countries. There are barriers such as lack of engagement with health services and language difficulties. Despite the importance of medication adherence for people who have migrated, there has been limited research. Aim: To investigate medication adherence among people of Indian ethnicity living with chronic diseases who have migrated to Australia. Methods: A cross sectional descriptive study was conducted in 2015, in the setting of one Hindu and two Sikh temples. Approximately 230 paper surveys were distributed, 139 returned. The surveys were anonymous and self-administered, adherence assessed through the validated 8-item Morisky Medication Adherence Scale. Findings: The majority of participants were born in India (54%), average age 50.1 years, average years living in Australia 17.5. Most participants reported taking their medications 83% of the time, 57% claiming to never miss. However, upon analysis of the survey, most had low adherence rates, particularly those younger and more recently migrated to Australia. Discussion: Poor adherence to medication leads to increased morbidity and death. It is a more significant problem in developing countries like India due to the paucity of health resources and accessibility to healthcare. This may explain the medication adherence practices and perceptions of participants who had more recently migrated to Australia. Conclusions: Health promotion and education regarding medication adherence in this group, community involvement and supportive workshops are outcomes of this study.